Veterinary medical guide to dog and cat breeds : 171 dog and 42 cat breeds /: 171 dog and 42 cat breeds. ([2012]) - Bell, Jerold S; Cavanagh, Kathleen E; Tilley, Lawrence P; Jr, Smith, Francis W. K
No abstract available